Fragmentos de DNA mitocondrial e nuclear nos estudos de taxonomia e filogenia de Ceroplastinae Atkinson (Hemiptera: Coccidae) - Rosa, Keila de Cassia Coelho (2016)
Molecular biology techniques, such as DNA sequencing to verify genetic polymorphisms, have been increasingly used in taxonomy studies and phylogenetic systematics. The mitochondrial gene cytochrome oxidase I (COI), chosen to be a universal marker of barcode of life (DNA barcoding), has been used in the identification of many living organisms, as well as for intraspecific variability studies, find cryptic species, among other uses. Phylogenetic studies generally combine two or more markers to increase the resolution at different taxonomic levels. Therefore, in this study, these techniques were employed to help taxonomy and phylogeny studies of scale insect species belonging to the Ceroplastinae Atkinson (Hemiptera: Coccidae). In the first chapter, DNA barcoding sequences were generated for four new species of the genus Ceroplastes Gray that were described morphologically. The integrated use of genetic and morphological data facilitated the establishment of the species, despite the phenotypic variability presented by some of the species. In the second chapter, fragments of COI and 28S genes were used to confirm that the Ceroplastes glomeratus Peronti species has two different forms, changing the behavior and morphological characters in different generations. In the third chapter, the molecular data obtained by sequencing of small fragments of COI and 28S genes grouped were used to construct phylogenetic hypothesis among the Ceroplastinae species studied here, testing groups that have been proposed previously for some species with distribution in the state of São Paulo, applying the methods of maximum likelihood and Bayesin inference.